Right Mindfulness in Teacher Education: Integrating Buddhist Teachings with Secular Mindfulness to Promote Racial Equity - Lindsay E. Romano; Doris F. Chang (MDPI AG, 2022)
Despite decades of reform efforts, disparities in schooling persist based on race, threatening the economic and social wellbeing of the United States. Why are there still significant opportunity gaps despite decades of reform efforts to curb inequities? For one, these efforts often overlook the internal habits of mind, or inner nature of inequity, and the ways in which educators may perpetuate racism through unexamined racial biases. Secular mindfulness and its Buddhist origins could help address these harmful habits of mind and transform systems by providing tools for educators to examine their internalized beliefs around race. Realizing the potential of these practices to combat racial inequities in the classroom requires building a stronger bridge between Eastern Buddhism and the individual psychological emphasis of Westernized mindfulness. This critical theoretical paper will examine opportunities for mindfulness interventions in the United States educational context to address inequities through a deeper integration with Eastern contemplative traditions. Implications for researchers and practitioners will be presented to explore how mindfulness practices in the West might be expanded and utilized in service of racial justice.